Challenges and opportunities in the Kampus Mengajar Program for basic literacy in South Aceh Junior High Schools - Bahrun; Mutmainnah (International Journal of Advances in Educational Research, 2025)
The Merdeka Belajar Kampus Merdeka (MBKM) policy is a strategic initiative by the Indonesian government to strengthen the synergy between higher education and primary-secondary education. One of its flagship programs is *Kampus Mengajar* (Teaching Campus), which aims to improve students’ basic literacy, particularly in underdeveloped and remote schools. However, preliminary observations suggest that the implementation of this program in South Aceh still faces significant challenges. Key issues include inadequate planning in teaching and learning, insufficient preparation of human resources, and weak coordination among universities, schools, and local education authorities. Moreover, participating students often lack the required competencies, their activities are not fully aligned with school needs, and teachers are not yet equipped with the skills to integrate literacy into classroom instruction. This study seeks to explore the challenges and opportunities for enhancing basic literacy in junior high schools through the Teaching campus program. A qualitative descriptive approach was employed, using in-depth interviews, focus group discussions (FGDs) with multiple stakeholders, and document analysis. The findings reveal that although the program holds considerable potential as an alternative strategy for improving basic literacy in secondary education, its implementation in South Aceh has not been optimal. Factors contributing to this include the limited experience and readiness of student-teachers, lack of intensive supervision by university mentors, and insufficient training for school teachers in applying literacy-based learning. Strengthening planning, human resource development, and program alignment between universities, schools, and local governments is essential to achieving the program’s intended outcomes.